2010
DOI: 10.4161/cbt.9.4.10748
|View full text |Cite
|
Sign up to set email alerts
|

The p300/CBP - associated factor is frequently down-regulated in intestinal-type gastric carcinoma and constitutes a biomarker for clinical outcome

Abstract: Reduced expression of PCAF plays an important role in the development of ITGC and correlates with a poor clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…We also demonstrated that loss of PCAF expression is an early event in colon cancer initiation, observed at the adenoma stage and maintained in carcinomas that correlates with CXCL12 silencing in human tumors. Loss of PCAF has already been described in pancreatic cancer, endometrial tumors or head and neck carcinomas, and has been implicated in different molecular processes regulating tumor initiation and/or progression [23–25]. Here we also show that forced-expression of PCAF in SW480 non-CXCL12 expressing cells, is a powerful inducer of CXCXL12, providing further evidence that in addition to methylation, level of promoter acetylation may participate to regulate CXCL12 expression in colon cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…We also demonstrated that loss of PCAF expression is an early event in colon cancer initiation, observed at the adenoma stage and maintained in carcinomas that correlates with CXCL12 silencing in human tumors. Loss of PCAF has already been described in pancreatic cancer, endometrial tumors or head and neck carcinomas, and has been implicated in different molecular processes regulating tumor initiation and/or progression [23–25]. Here we also show that forced-expression of PCAF in SW480 non-CXCL12 expressing cells, is a powerful inducer of CXCXL12, providing further evidence that in addition to methylation, level of promoter acetylation may participate to regulate CXCL12 expression in colon cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…Inhibitors of SRC kinase activity have been used to treat gastric cancer (Nam et al, 2013). KAT2B is a histone lysine acetyltransferase that regulates gene transcription via interaction with p300/CREB-binding protein (Zhu et al, 2009); down-regulation of KAT2B promotes intestinal-type gastric cancer progression and is correlated with a poor clinical outcome (Ying et al, 2010). NR3C1 encodes glucocorticoid receptor which is associated with several biological process including inflammation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PCAF has been found to be down-regulated in HCC tissues compared with the adjacent non-tumor tissues and significantly associated with malignant portal vein invasion and poor survival of HCC patients [32]. PCAF expression has also been reported to be downregulated in HCC, gastric cancer and ovarian cancer [33]. In esophageal SCC, loss of PCAF locus correlated with advanced tumor stage and metastasis.…”
Section: Lysine Acetyltransferases Families and Their Link To Cancermentioning
confidence: 99%